The fever of English 2.0 in Indonesia: University students’ and faculty members’ attitudes towards English in different multilingual landscapes - Abdurahman, Nur Hafiz; Gandana, Isti Siti Saleha; Novianti, Nita (Universitas Pendidikan Indonesia, 2018)
The global spread of English has become a widely felt phenomenon, arousing different perceptions and attitudes among those who encounter it. The dominant use of English in virtual spaces has led to the emergence of ‘English 2.0,’ which has been perceived as a new concept of learning English involving networked learning and the use of digital technologies. This study explores Indonesian university students’ and faculty members’ attitudes towards the use of English in both face-to-face and virtual contexts. Adopting a mixed methods approach, it involved two hundred and fifty-one respondents through which questionnaires were distributed and completed. Responses to Likert-scale items were analysed using a paired-samples t-test of SPSS, while open-ended responses were used to yield a more in-depth analysis. The results show that there were mixed attitudes towards English among the respondents. This study suggests that while virtual domains can provide a space for learning and practicing English, a beneficial utilisation of the language ultimately depends on how English language learning is planned and designed.